KELAS "IBU HEBAT" (IBU HAMIL EDUKASI BAYI DAN BALITA): PENCEGAHAN MALARIA DAN STUNTING DIMULAI DARI DALAM KANDUNGAN - Hermayani; Inggrit Rita Uli Manik; Selina Boseren (Health Care : Journal of Community Service, 2026)
Malaria and stunting are interconnected major public health issues in eastern Indonesia, particularly in Papua. Malaria infection during pregnancy can cause severe anemia and Low Birth Weight (LBW), which are primary risk factors for stunting in children. A situational analysis in the Biak Kota Health Center service area in early 2026 indicated ongoing malaria cases among pregnant women and a stunting prevalence requiring intervention from pregnancy. The objective of this community service activity is to enhance the knowledge and empowerment of pregnant women and mothers of toddlers through the "Great Mother" Class (Pregnant Women Educate Babies and Toddlers), focusing on malaria and stunting prevention starting from the womb. The method employed was education and small group discussions using leaflets and nutritional counseling, executed in March 2026. Activity evaluation was conducted via pre-test and post-test. The results showed a significant increase in participants' knowledge. The average pre-test score was 64.22 (with 44% of participants failing), which increased to 90.7 in the post-test, with 100% of participants achieving a passing category. It can be concluded that the "IBU HEBAT" Class is highly effective in breaking the stunting risk chain through malaria prevention and ANC optimization.